2022
DOI: 10.1101/2022.02.25.482019
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DLK-dependent biphasic reactivation of herpes simplex virus latency established in the absence of antivirals

Abstract: An understanding of the molecular events that regulate entry of herpes simplex virus type 1 (HSV-1) into a latent infection of neurons and subsequent reactivation requires model systems. However, establishing a latent-like infection in cultured neurons is problematic as the release of any infectious virus can potentially superinfect the cultures. Here, we describe a new reporter virus, HSV-1 Stayput-GFP, that is defective for cell-to-cell spread. Use of this virus permits the establishment of a quiescent infec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 129 publications
(196 reference statements)
0
9
0
Order By: Relevance
“…However, during the productive replication cycle, the VP16 gene is expressed with late kinetics. During Phase I, VP16, like other late genes, is expressed in the absence of viral DNA replication 33,36,37 . Further, work from the Sawtell and Thompson labs has shown that elements within the VP16 promoter can function prior to immediate-early gene expression, specifically in neurons, and are involved in the initial depression of viral gene expression during acute infection of the ganglia 55,65 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, during the productive replication cycle, the VP16 gene is expressed with late kinetics. During Phase I, VP16, like other late genes, is expressed in the absence of viral DNA replication 33,36,37 . Further, work from the Sawtell and Thompson labs has shown that elements within the VP16 promoter can function prior to immediate-early gene expression, specifically in neurons, and are involved in the initial depression of viral gene expression during acute infection of the ganglia 55,65 .…”
Section: Discussionmentioning
confidence: 99%
“…So far, the host proteins known to function during Phase I to induce lytic gene expression are DLK and JNK 32,34,36,37 . Experiments performed here with the DLK inhibitors suggest that DLK may be downstream of STING activation.…”
Section: Studies From Our Lab and Others Mapping The Time Of Lytic Ge...mentioning
confidence: 99%
See 3 more Smart Citations